2018
DOI: 10.1002/jcp.26943
|View full text |Cite
|
Sign up to set email alerts
|

Identification of key genes and pathways associated with osteogenic differentiation of adipose stem cells

Abstract: Adipose stem cells (ASCs) are considered a great alternative source of mesenchymal stem cells (MSCs) and have shown great promise on tissue engineering and regenerative medicine applications, including bone repair. However, the underlying mechanisms regulating the osteogenic differentiation of ASCs remain poorly known. Gene expression profiles of GSE63754 and GSE37329 were downloaded from gene expression omnibus database. R software and Bioconductor packages were used to compare and identify the differentially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…Comparison of datasets could allow the identification of key genes presented in different osteogenic differentiation protocols ( Yang et al, 2019 ) which may indicate an essential role in the differentiation process. Beside that, re-analysis of microarray data from osteogenic differentiated adipose derived-MSC ( Berdasco et al, 2012 ; Daniunaite et al, 2015 ) showed that 142 and 69 genes were up and downregulated, respectively, in both datasets ( Zhao et al, 2018 ). GO and pathway analysis of DEG indicated that they were enriched in terms associated with “ECM organization,” “angiogenesis,” “Wnt protein binding,” “FXR/RXR activation,” and “adipogenesis pathway,” among others.…”
Section: Gene Expression Profile In Osteogenesis Of Mscmentioning
confidence: 99%
“…Comparison of datasets could allow the identification of key genes presented in different osteogenic differentiation protocols ( Yang et al, 2019 ) which may indicate an essential role in the differentiation process. Beside that, re-analysis of microarray data from osteogenic differentiated adipose derived-MSC ( Berdasco et al, 2012 ; Daniunaite et al, 2015 ) showed that 142 and 69 genes were up and downregulated, respectively, in both datasets ( Zhao et al, 2018 ). GO and pathway analysis of DEG indicated that they were enriched in terms associated with “ECM organization,” “angiogenesis,” “Wnt protein binding,” “FXR/RXR activation,” and “adipogenesis pathway,” among others.…”
Section: Gene Expression Profile In Osteogenesis Of Mscmentioning
confidence: 99%
“…To better understand the impact of n-3 PUFAs on the transcriptome of the developing bone, we performed RNA-seq analysis of the bones of mice whose PUFA intake originated from different dietary sources. Although a few studies have used RNA-seq analysis to reveal the DE genes in skeletal tissue [45][46][47], as far as we know, this is the first study that uses RNA-seq to study the effect of dietary n-3 PUFAs on bone transcriptome in vivo.…”
Section: Transcriptional Regulation Of Bone By Different Sources N-3 mentioning
confidence: 99%
“…ASCs have self-renewal property as demonstrated by the Colon Forming Unit formation (CFU-F) assay [ 39 , 40 , 41 , 66 ]. They have multipotency property, as they have the capability to differentiate toward different mesenchymal cell lineages [ 39 , 65 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 ]. Interestingly, ASCs also have a higher responsiveness to inducers of non-mesenchymal cell lineages differentiation [ 39 , 65 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 ].…”
Section: Adipose Stem Cellsmentioning
confidence: 99%
“…The osteogenic differentiation of ASCs, may be achieved by using inducing osteogenic factors (e.g., dexamethasone, ascorbic acid/ascorbate 2-phosphate, and β-glycerophosphates, vitamin D3, transforming growth factor-β and bone morphogenetic proteins), in growth culture medium. As a consequence ASCs express early osteogenic markers (alkaline phosphatase and BMPII) and later osteogenic markers (osteocalcin, osteogenic transcription factor Runx2, osteonectin, osteopontin, bone morphogenic protein-2, and Osterix) [ 41 , 73 , 101 , 111 ].…”
Section: Adipose Stem Cellsmentioning
confidence: 99%